2014
DOI: 10.1373/clinchem.2014.221671
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Human Lipocalin as an Antibody Mimetic: Application to Analysis of the Small Peptide Hormone Hepcidin

Abstract: ical Centre (Nijmegen, the Netherlands) that among others offers hepcidin measurements on a fee-per-sample basis to the medical, scientific, and pharmaceutical communities through a service unit called hepcidinanalysis.com.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Direct hepcidin inhibitors, e.g., neutralizing antibodies, have demonstrated efficacy in increasing circulating and available iron for erythropoiesis, reversing anemia and increasing responsiveness to ESAs in mouse models of ACI and increasing serum iron concentration and erythropoiesis in monkeys . LY2787106, a monoclonal anti‐hepcidin antibody (Eli Lily), has been developed and proposed as potential therapy in conditions of excess hepcidin, recently demonstrating high tolerability, transient iron mobilization, and increased reticulocytosis in a Phase I study of cancer‐related anemia patients . PRS‐080, a PEGylated anticalin with specific binding and neutralization of hepcidin (Pieris Pharmaceuticals), demonstrated suppression of hepcidin activity in vitro and in mice with decreased hepcidin and transiently increased transferrin saturation at doses above 0.4 mg/kg in a Phase I study in healthy volunteers, warranting further investigations in anemic patients.…”
Section: Methods For Pharmacological Reduction Of Hepcidinmentioning
confidence: 99%
“…Direct hepcidin inhibitors, e.g., neutralizing antibodies, have demonstrated efficacy in increasing circulating and available iron for erythropoiesis, reversing anemia and increasing responsiveness to ESAs in mouse models of ACI and increasing serum iron concentration and erythropoiesis in monkeys . LY2787106, a monoclonal anti‐hepcidin antibody (Eli Lily), has been developed and proposed as potential therapy in conditions of excess hepcidin, recently demonstrating high tolerability, transient iron mobilization, and increased reticulocytosis in a Phase I study of cancer‐related anemia patients . PRS‐080, a PEGylated anticalin with specific binding and neutralization of hepcidin (Pieris Pharmaceuticals), demonstrated suppression of hepcidin activity in vitro and in mice with decreased hepcidin and transiently increased transferrin saturation at doses above 0.4 mg/kg in a Phase I study in healthy volunteers, warranting further investigations in anemic patients.…”
Section: Methods For Pharmacological Reduction Of Hepcidinmentioning
confidence: 99%
“…A subsequent study of the same group demonstrated that an anti-human hepcidin antibody per se was able to increase iron levels and to stimulate erythropoiesis in humanized hepcidin knock in mice, but also affected iron homeostasis similarly in cynomolgus monkeys [49]. In a comparable fashion small, highly specific hepcidin binding peptides, so called anticalins, are currently studied for their therapeutic potential to combat the biological activity of hepcidin in vivo [50].…”
Section: Treatmentmentioning
confidence: 99%
“…A subsequent study of the same group demonstrated that an anti-human hepcidin antibody per se was able to increase iron levels and to stimulate erythropoiesis in humanized hepcidin knock in mice, but also affected iron homeostasis similarly in cynomolgus monkeys [49]. In a comparable fashion small, highly specific hepcidin binding peptides, so called anticalins, are currently studied for their therapeutic potential to combat the biological activity of hepcidin in vivo [50].Circulating hepcidin can be bound and neutralized by NOX-H94, a mirror-image Lenatiomeric oligoribonucleotide, called Spiegelmer. Application of NOX-H94 prevented the inflammation induced reduction of serum iron levels in cynomolgus monkeys and was recently studied in health volunteers injected with LPS.…”
mentioning
confidence: 99%